2022
DOI: 10.3928/01477447-20220105-02
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Orthopedic Trauma Surgery

Abstract: Racial discrepancies among patients in the United States undergoing orthopedic trauma surgery have not been investigated. Issues relating to socioeconomic status and access to care have played a role in the health outcomes of racial groups. In orthopedic surgery, recent joint arthroplasty literature has shown significant racial differences in the use of elective joint arthroplasty. Furthermore, studies also suggest increased rates of early complication in racial minority groups. In general, little information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A recent NSQIP study analyzing patients undergoing orthopaedic trauma surgery has found higher frequencies of deep wound infection (0.5% vs 0.3%, P = .002) among Black patients, although with decreased mortality and postoperative transfusion. 44 Prior studies evaluating complications after ankle fracture surgery have not examined the effect of ethnicity on adverse outcomes. 4 , 7 , 9 , 28 , 30 , 32 , 34 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent NSQIP study analyzing patients undergoing orthopaedic trauma surgery has found higher frequencies of deep wound infection (0.5% vs 0.3%, P = .002) among Black patients, although with decreased mortality and postoperative transfusion. 44 Prior studies evaluating complications after ankle fracture surgery have not examined the effect of ethnicity on adverse outcomes. 4 , 7 , 9 , 28 , 30 , 32 , 34 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…A recent NSQIP study analyzing patients undergoing orthopaedic trauma surgery has found higher frequencies of deep wound infection (0.5% vs 0.3%, P = .002) among Black patients, although with decreased mortality and postoperative transfusion. 44 Prior studies evaluating complications after ankle fracture surgery have not examined the effect of ethnicity on adverse outcomes. 4,7,9,28,30,32,34,41 Smokers in certain age groups were at a higher risk of developing deep wound infections and wound dehiscence than the baseline OR of 2.34 and 2.43 for those complications respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are disparities in the use of discretionary orthopaedic surgical care such as hip and knee arthroplasty for osteoarthritis by race and ethnicity [9,29,32]. What is unclear is the degree to which these differences arise from factors worthy of correction such as distrust, limited access, affordability, or limited awareness of the available health benefits of arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…a survey study of ambulatory patients in the same institution seeking consultation for elective orthopaedic treatment had a distribution of 78% White, 5% East Asian, 4.5% Black, 4.3% South Asian, and 7.8% other ethnicity [ 49 ]. A number of American studies have demonstrated that racial/ethnic minority patients have higher risk of adverse events for both planned and unplanned orthopaedic surgery [ 50 54 ]. Corresponding evidence in the Canadian orthopaedic population is lacking, though there is evidence that Indigenous Canadians have increased rates of postoperative complications when undergoing a variety of surgical procedures [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%